A graphical user interface for the Fastcomp software - Patrícia Carla Teixeira Gonçalves (2006)
FastComp is a computational tool used in mechanical engineering for the determination of the forces that a composite bolted joint subjected to multiaxial loads supports until fracture occurs. The main intention of the present work was the development of a graphical user interface (GUI) for the referred software that allows its parameterization and the visualization of its results.Using VTK, a computational library for graphical objects, visualization and image processing; C#, an object-oriented programming language; and the design principles of a good human/computer interaction, a graphical interface was developed as an efficient and effective means of interaction with the FastComp software.